2013
DOI: 10.2169/internalmedicine.52.8961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liraglutide, a Human Glucagon-like Peptide-1 Analogue, on Body Weight, Body Fat Area and Body Fat-related Markers in Patients with Type 2 Diabetes Mellitus

Abstract: Objective To evaluate the effects of six-month liraglutide treatment on body weight, visceral and subcutaneous fat and related markers in Japanese type 2 diabetic patients. Methods A total of 59 patients with type 2 diabetes were treated with liraglutide (0.3 mg/day for ! 1 week and then 0.6 mg/day for ! 1 week, gradually increasing the dose to 0.9 mg/day) for six months. Changes in body weight, body mass index (BMI), HbA1c, the fasting blood glucose level, visceral and subcutaneous fat areas, hepatic and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 19 publications
5
53
0
Order By: Relevance
“…Prior studies suggested that GLP-1 receptor agonists, such as liraglutide and exenatide, would improve liver steatosis in animal models (27,28), in human case series (29), and in prospective nonrandomized trials (30,31). However, in the setting of the randomized controlled trial Liraglutide Efficacy and Action in Diabetes (LEAD)-2 substudy, there was a nonsignificant trend toward a reduction in liver steatosis as assessed by computed tomography with the liver-tospleen attenuation ratio, but only for the 23 patients receiving higher doses (1.8 mg) of liraglutide (11,32).…”
Section: Effect Of Insulin Glargine and Liraglutide On Mr-based Biomamentioning
confidence: 99%
“…Prior studies suggested that GLP-1 receptor agonists, such as liraglutide and exenatide, would improve liver steatosis in animal models (27,28), in human case series (29), and in prospective nonrandomized trials (30,31). However, in the setting of the randomized controlled trial Liraglutide Efficacy and Action in Diabetes (LEAD)-2 substudy, there was a nonsignificant trend toward a reduction in liver steatosis as assessed by computed tomography with the liver-tospleen attenuation ratio, but only for the 23 patients receiving higher doses (1.8 mg) of liraglutide (11,32).…”
Section: Effect Of Insulin Glargine and Liraglutide On Mr-based Biomamentioning
confidence: 99%
“…Liraglutide is effective in patients with maturity-onset diabetes of the young (MODY) 3, and produces lower hypoglycemic risk than glimepiride [9] . Moreover, liraglutide has also been used as an anti-obesity therapy [10] . In addition, liraglutide is currently applied in the treatment of other insulin resistance-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…High body mass index (BMI) is an independent risk factor for cardiovascular diseases and all-cause mortality for people with T2D [12, 13]. High BMI, also involved in the pathogenesis of T2D, can complicate the treatment of T2D by altering lipid levels, increasing insulin resistance, and raising blood glucose levels [13].…”
Section: Introductionmentioning
confidence: 99%